Assessment of Engine Performance and Emissions Using Palm Oil–Banana Peel Biodiesel Blend in CI Engines - Suardi; Mahmuddin, Faisal; Sitorus, Chris Jeremy Verian; Sitorus, Chris Jeremy Verian; Hariyono; Uswah Pawara, Muhammad; Hijriah; Kustiwansa, Harlian; Zainal, Muhammad (International Journal of Marine Engineering Innovation and Research, 2025)
The global need for renewable energy has encouraged the use of biodiesel from organic waste as an alternative to hydro-carbon fuels. This study focuses on evaluating the performance of a CI diesel engine using a fuel blend made from palm oil and banana peel oil. The objective is to determine the optimal blend in terms of fuel properties, engine performance, and exhaust emissions. The biodiesel is produced using the transesterification method for palm oil and a heating extraction process for banana peel oil. Engine tests are carried out on a Yanmar TF85-ME single-cylinder diesel engine using three fuel types: B0 (Dex-lite), BBO-30 (30% banana peel oil and biodiesel), and BBO-50 (50% blend). Fuel characterization showed that BBO-50 had the highest viscosity (4.23 cSt) and density (925 kg/m³), while BBO-30 had the highest calorific value (45.1 MJ/kg). Performance testing revealed that BBO-30 achieved the highest torque (7.26 Nm), lowest SFC (367.4 g/kWh), and highest thermal efficiency (22.4%). Emission tests showed that BBO-50 produced the lowest CO and NOx emissions, while BBO-30 had the highest CO2 emis-sion, indicating more complete combustion. Based on these results, BBO-30 is recommended for optimal engine efficiency, while BBO-50 is more suitable for lower emissions.